Pengaruh Perubahan Pendapatan Yang Dimoderasi Oleh Siklus Kas Operasi Dalam Memprediksi Akrual - Muhammad Nur Ihkwansyah; Nurzi Sebrina (Universitas Negeri Padang, 2020)
The purpose of this research is to examine the effect of operating cash cycle in moderating the relationship of revenue changes and accruals. This research is classified as causative research with a quantitative approach. The population are manufacturing companies listed on the Indonesian Stock Exchange period of 2016 to 2018. By using purposive sampling method, there were 43 companies as the research’s sample. The type of data used is secondary data obtained from the official site of the Indonesia Stock Exchange and company’s official website. The hypotheses were tests using panel regression analysis. The results indicate that revenue changes has not significant effect on accrual, also operating cash cycle is not able to strengthen or weaken the relationship between revenue changes and accruals